Facial expression quantification and analysis - Ramya Sridharan (2008)
Visual Image Processing is extensively used in the field of medicine and bio-medical engineering. It has become almost indispensable in many bio-medical applications. Visual image processing has two major divisions: Analysis and Synthesis. (i) Analysis refers to the extraction and quantification of data from available images. (ii) Synthesis refers to the construction of images from available information. This dissertation mentions some of the latest techniques available in the above field and proposes two design techniques that exceed the performance of their peers in both technical aspects and applications.